PENGARUH PENGERINGAN DAN SUHU PENYIMPANAN TERHADAP DAYA HIDUP BIJI KEMUNING (MURRAYA PANICULATA) - WULIJARNI, N.; SOETJIPTO, SOETJIPTO (Research Center for Biology-Indonesian Institute of Sciences, 1988)
N.WULIJARNI-SOETJIPTO.1988. Effect of drying and storage temperature on the viability of kemuning(Murraya panicuhta) seeds, Berita Biologi 3(8): 424 - 429.Seeds of kemuning Murraya paniculata (L.) Jack) were dried under room temperature (28°±2°C),and then stored for a duration of 9 weeks at 28°, 10°, 4° and - 10°C. The seeds remained fully viable when the moisture content was reduced to 5%. After storage at 10° or 4°C the seeds having 5% moisture content remained almost fully viable.Their viability decreased to around 60% at - 10°C, and less than 40% at 28°C.Seeds having higher moisture contents still maintained their viability after being stored at 10°C. However, they lost their viability when stored at higher or lower temperatures.It appeared that the seeds contained much higher percentage of saturated fatty acids compared with the unsaturated fatty adds. It is concluded that the kemuning seeds do not tend to follow the behaviour of true orthodox seeds,since they do not seem to withstand subfreezing temperature although they may toleratev drying.",